A Calibration Method for the Errors of Ring Laser Gyro in Rate-Biased Mode - Zengjun Liu; Lei Wang; Kui Li; Jingxuan Ban; Meng Wang (Sensors, 2019)
Ring laser gyro (RLG) can work in mechanically dithered mode or rate-biased mode according to the working state of the inertial navigation system (INS). It can change from one mode to the other by receiving outer instructions. To evaluate the performance of RLG in rate-biased mode, an inertial measurement unit (IMU) based on RLG is installed on a dual-axis turntable, the turntable offers a constant angular velocity to the RLGs, in that way RLG can work in the rate-biased mode. A calibration method is proposed to calibrate the scale factor error, misalignments and constant bias of RLG in rate-biased mode, experiment results show that the differences of scale factor of the three gyros in two modes are 9 ppm, 7 ppm and 3.5 ppm, the constant biases of the three RLGs in rate-biased mode are also different from that in mechanically dithered mode with the difference of 0.017°/h, 0.011°/h and 0.020°/h, the input axis misalignment angle of RLGs in different modes also changed. What is more, a calculation method of angle random walk (ARW) of RLG in rate-biased mode is also presented. Experimental results show that the ARW of the RLG in rate-biased mode is about one third of that in mechanically dithered.